Listening for commissioning: A participatory study exploring young people's experiences, views and preferences of school‐based sexual health and school nursing. Issue 1 (3rd August 2017) - Aranda, Kay; Coleman, Lester; Sherriff, Nigel S; Cocking, Chris; Zeeman, Laetitia; Cunningham, Liz
Abstract : Aims and objectives: To explore the experiences, views and preferences of young people aged 11–19 years regarding school‐based sexual health and school nursing to inform commissioning and delivery for one local authority area in England during 2015. Background: Promoting sexual health for young people remains a challenging, even controversial, but important public health issue. Concerns regarding accessibility, acceptability and efficacy in school‐based sexual health and school nursing are evident in the literature. Additionally, a complex public health policy context now governs the funding, provision and delivery of sexual health and school nursing, which potentially presents further challenges. Design: A qualitative, participatory design was used to explore sexual health and school nursing. Data were generated from 15 focus groups ( n  = 74), with young people aged 11–19 years, in educational‐based settings in one local authority area in England. Results: The resultant themes of visibility in relation to sexual health education and school nursing revealed both the complex tensions in designing and delivering acceptable and appropriate sexual health services for young people and the significance of participatory approaches. Conclusion: Our study shows the importance of participatory approaches in working with young people to clearly identify what they want and need in relation to sexual health. The findings also confirm the ways in which school‐based sexual health remains challenging but requires a theoretical and conceptual shift. This we argue must be underpinned by participatory approaches. Relevance to clinical practice: School nurses have always had a significant role to play in promoting positive sexual health for young people and they are exceptionally well placed to challenge the risk‐based cultures that frequently dominate school‐based sexual health. A shift of debates and practices towards the promotion of positive sexual health cultures though previously argued for now requires the active engagement and involvement of young people.